In vitro testing of drug combinations employing nilotinib and alkylating agents with regard to pretransplant conditioning treatment of advanced-phase chronic myeloid leukemia - Radujković, Aleksandar; Luft, Thomas; Dreger, Peter; Ho, Anthony Dick; Jens Zeller, W.; Fruehauf, Stefan; Topaly, Julian (Cancer chemotherapy and pharmacology, 2014)
The prognosis of patients with advanced-phase chronic myeloid leukemia (CML) remains dismal despite the availability of targeted therapies and allogeneic stem cell transplantation (allo-SCT). Increasing the antileukemic efficacy of the pretransplant conditioning regimen may be a strategy to increase remission rates and duration. We therefore investigated the antiproliferative effects of nilotinib in combination with drugs that are usually used for conditioning: the alkylating agents mafosfamide, treosulfan, and busulfan.